An Unusual Occurrence of Colisepticemia in Budgerigars (Melopsittacus undulatus) - Priya, P.M.; Pillai, Deepthi S.; Rameshkumar, P.; Senthamilselvan, P. (International Journal of Poultry Science, 2008)
A rare case of colisepticemia in budgerigar was reported from Kerala. Overcrowding coincident with increased noise and low light levels appeared to be the predisposing factors.